THE USE OF AUGMENTED REALITY (AR) MEDIA TO ENHANCE STUDENTS’ VOCABULARY MASTERY AT SEVENTH GRADE STUDENTS OF SMP NEGERI 7 TARAKAN - Natalia, Merry Christin; Fitriawati, Fitriawati (Borneo Journal of English Language Education, 2022)
This research aimed to find out the average difference of Augmented Reality students' learning results in enhancing vocabulary mastery understanding about describing animals. The subjects of this research were 26 students from grades 7-6 of SMP Negeri 7 Tarakan in the academic year 2021/2022 using the pre-experimental method. This was research with One Group Pretest-Posttest design. Sample selection using Purposive Sampling. The instruments were a vocabulary test in the pretest and posttest to measure students’ achievement in the learning process during treatments. The hypothesis was tested using Parametric Paired Sample T-Test. Paired Sample T-Test showed that the average students score in Pretest and Posttest. This is evidenced by the results of the average score of students. The average score in the Pretest was 53,12 and the average score in the posttest was 72,81. The results show the posttest was higher than the Pretest value. This shows that there was a significant difference in the students' vocabulary mastery at the pretest and posttest. Other than that, the value of N Gains both pre-test and post-test showed 0.42 is categorized as Normal. In addition, the paired sample t-test test results showed that -t-test (-7.010) is smaller than -t-table (-2.060). Based on the test results, the researchers concluded that the use of Augmented Reality media was proven to be effective in enhancing vocabulary comprehension learning outcomes in describing animals in the seventh grade of SMP Negeri 7 Tarakan